A First Rock Glacier Inventory for the Bolivian Andes. (8th October 2014) - Rangecroft, Sally; Harrison, Stephan; Anderson, Karen; Magrath, John; Castel, Ana Paola; Pacheco, Paula
ABSTRACT Rock glaciers in the arid Bolivian Andes are potentially important water sources, but little is known about their spatial distribution and characteristics. We provide the first rock glacier inventory for the region (15–22°S), based on mapping using remote sensing data in Google Earth, supported by field validation. Of the 94 rock glaciers identified, 57 per cent were classified as active (containing ice) and the remaining as relict (not containing ice). The majority (87%) have a southerly aspect (SE, S and SW), and the rock glacier length and area averages were 500 m and 0.12 km2, respectively. We approximate the lower limit of permafrost to be at 4700 m in the Bolivian Andes, with the mean minimum altitude of rock glacier fronts estimated to be 4980 m for active rock glaciers, and about 100 m lower for relict rock glaciers. The inventory provides an important first step towards assessing the spatial distribution of regional permafrost as well as information to allow permafrost‐based water resources in the Bolivian Andes to be understood against a backdrop of severe glacier recession. Copyright © 2014 John Wiley & Sons, Ltd.